Inhibition of thymic stromal lymphopoietin production by FK3453 - Ryosuke Segawa; Ryosuke Ishihara; Masahiro Hiratsuka; Noriyasu Hirasawa (Elsevier, 2022)
To prevent the onset and aggravation of allergic diseases, it is necessary to modulate excessive Th2-type immune responses. It is well accepted that thymic stromal lymphopoietin (TSLP) plays important roles in the change of Th1/Th2 balance to Th2 dominance and would be a druggable target. In this study, using a drug repositioning strategy, we identified 6-(2-amino-4-phenylpyrimidine-5-yl)-2-isopropylpyridazin-3(2H)-one (FK3453) as a novel inhibitor of TSLP production. FK3453 inhibited constitutive production of TSLP in the KCMH-1 mouse keratinocyte cell line and 12-O-tetradecanoylphorbol-13-acetate (TPA)-induced one in PAM212 cells. FK3453 also inhibited TSLP mRNA expression induced by a mixture of tumor necrosis factor alpha (TNF-α), interleukin (IL)-4, fibroblast-stimulation lipopeptide-1, and protease activated-receptor agonist and TPA in normal human epidermal keratinocytes (NHEKs). Although FK3453 inhibited TPA-induced IL-33 expression in NHEKs in addition to TSLP, it did not inhibit TNF-α and IL-6 production. In addition, FK3453 did not inhibit MAP kinase (ERK) phosphorylation. We have confirmed that topical treatment with FK3453 inhibited TSLP production in the lipopolysaccharide-induced air pouch-type inflammation model. FK3453 could be a lead compound for a novel type of medicine which prevents the onset and aggravation of allergic diseases.